Secure Base Leadership in military training: enhancing organizational identification and resilience through work engagement - Navas-Jiménez, María C.; Laguía, Ana; Recio, Patricia; García-Guiu, Carlos; Pastor, Alberto; Edú-Valsania, Sergio; Molero, Fernando; Mikulincer, Mario; Moriano, Juan A. (Frontiers in Psychology, 2024)
This study applies the Job Demands-Resources model (JD-R) to the associations between Secure Base Leadership (SBL) and organizational identification and resilience and the potential mediating role of work engagement. Using a structural equation model with the partial least squares technique, data collected from 363 cadets of the General Military Academy of the Army in Zaragoza, Spain, were analyzed. Participants, belonging to the second (n = 170; 46.8%) and third (n = 193; 53.2%) years of training, with a gender distribution of 84% male and 16% female, evaluated their respective section chief captain and completed measures tapping work engagement, organizational identification, and resilience. Findings revealed a positive relationship between SBL and work engagement, with the latter acting as a significant mediator between SBL and organizational identification and resilience. These findings not only validate the JD-R model but also highlight the personal and organizational benefits of SBL in a military context and its relevance for the professional development and well-being of cadets.